Non‐canonical STAT3 function reduces REDD1 transcription. (7th December 2022) - Köhler, Nadine; Wundrack, Nicole; Schulz, Svenja; Bartonitz, Florian; Schaper, Fred; Dittrich, Anna
Abstract : The transcription factor STAT3 is a potent activator of transcription, but evidence exists that STAT3 can also repress gene expression. However, little is known about the molecular mechanisms involved in STAT3‐dependent gene repression. Notably, STAT3 reduces the expression of the stress‐induced mTOR inhibitor REDD1 by reducing REDD1 mRNA transcription. Here, we determined the functional domains of STAT3 responsible for the reduction of REDD1 mRNA and protein expression. Within STAT3, the N‐terminal domain and tyrosine 705 are crucial for STAT3‐dependent reduction of REDD1 expression. Interestingly, binding of STAT3 to canonical STAT‐binding sides within the REDD1 promoter is not necessary for STAT3‐mediated reduction of REDD1 expression. Still, STAT3 is recruited to the REDD1 promoter upon stimulation with IL‐6, and reduces REDD1 promoter activity. The reduction of REDD1 expression is specific for STAT3, as neither expression nor activation of STAT1 reduces REDD1 mRNA and protein expression. In summary, we present a novel, non‐canonical STAT3‐dependent mechanism for reducing gene expression. This transcriptional repression increases the functions of STAT3 proteins beyond classical transcriptional activation of cytokine‐regulated target genes to a more complex function in modulating gene expression in immunity and cellular stress. Abstract : STAT3 is an important activating transcription factor. There is increasing evidence that STAT3 also reduces the expression of certain genes. We report that STAT3 reduces the expression of the mTOR inhibitor REDD1. This inhibition is independent of STAT3 binding to canonical STAT3 DNA‐binding sites, but depends on STAT3 tyrosine phosphorylation. This transcriptional repression extends the functions of STAT3 beyond transcriptional activation to a complex function in modulating gene expression.